THE UTILIZATION OF PHYSICS LABORATORY IN SMA NEGERI 1 ENDE - Maria Fatima End Kedang; Aloisius Harso; Ana Silfiani Rahmawati (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This study was conducted with the aim of describing the use of physics laboratory facilities in terms of the availability of facilities and the use of physics laboratories in learning. The type of research used in this research is qualitative descriptive analysis. The data analysis techniques used were documentation, interviews, and questionnaires. The data collected was then analyzed using 3 activity lines, namely: (1) data reduction, (2) data presentation, and (3) drawing conclusions. Based on the results of the data analysis, the following conclusions were found. First, the availability of physical laboratory facilities is sufficient. Second, the use of physics laboratories in physics learning is currently effective.